Evaluation of The Implementation of The Dashat (Healthy Kitchen Overcomes Stunting) and Gong Ceting (Gotong Royong to Prevent Stunting) Program to Prevent and Fulfill Nutrition of Stunting Toddler in Tieng Village, Wonosobo District - Lial Khusna; Reni Pawestuti Ambari Sumanto (BELIA Early Childhood Education Papers, 2024)
This research aims to determine the evaluation of the implementation of the stunting reduction program, namely the Healthy Kitchen to Overcome Stunting and Mutual Cooperation to Prevent Stunting program in Tieng Village, Wonosobo Regency, by analyzing the evaluation of input, process and output. The method used is a descriptive qualitative method. The subjects in this research were 11 people consisting of PKK cadres, Posyandu cadres, Tieng Village Midwives, students, nutritionists, village officials and program recipients. Data collection techniques are carried out through interviews and documentation. Method triangulation by conducting interviews with nutritionists at the Kejajar Community Health Center, Tieng Village Officials, and parents of program recipients. Data analysis techniques are carried out through data reduction, data presentation, and verification or drawing conclusions. Evaluation of the DASHAT program shows obstacles to input evaluation in the form of a lack of budget from program organizers, time constraints for program implementation, delays in handling stunted children, as well as the need to improve facilities and infrastructure. The output during the implementation of DASHAT is influenced by input and process, the output from the implementation of the DASHAT program is still not able to reduce stunting cases in Tieng Village. The evaluation of the Gong Ceting program experienced obstacles in the input evaluation in the form of a lack of facilities and infrastructure, long distance from the campus to the focal village, internet network problems when participating in the MURI record zoom, as well as short implementation time, but the output of the Gong Ceting program showed success marked by solutions MURI record by serving 14,000 portions of nutritious food for stunted children and declaring 10 stunting locus villages in Wonosobo Regency.